Zakat Fitrah di Lembaga Pendidikan Perspektif Mazhab Syafi’i dan Mazhab Hanafi - Rohmawati, Kiki Ayu (Fakultas Syariah, 2015)
Zakat is the third of pillars of Islam, which is very important for improving the existence of Muslim worship beside of prayer and fasting, so zakat fitrah is carried so much by Elementary Schools and Islamic Elementary Schools to be used as a basic learning by way of zakat payment practice in schools. There are two of education institutions carried by the author. They are Bandar II Elementary School and Ihsan al-Bandar Islamic Elementary School, Kedung Mulyo village, Bandar Kedung Mulyo sub-district, Jombang. In November 2014 ago. The main purpose of this study is to understand the practice of zakat fitrah applied in Elementary School and Islamic Elementary School in Bandar Kedung Mulyo Village, Bandar Kedung Mulyo sub-district, Jombang, and to review the law of Syafi’i and Hanafi sect perspective. In this study uses the type of empirical research with qualitative approach. Most of the primary data collected through semi-structured interviews and field observations. Literature and related documentation of this issue are used as the secondary data. After collecting the data, then analyze it by using qualitative descriptive method. Based on the analysis, the conclusion is zakat fitrah in Elementary School and Islamic Elementary School of Bandar Kedung Mulyo has different characteristics and practices in collecting zakat, zakat distribution, and the time of collection and dividing of zakat. The difference is because of Bandar II Elementary School tends to be proportional to follow the Syafi’i and Hanafi sect, whereas in al-Ihsan Islamic Elementary School tends to follow or taqlid at one sect, that is Syafi’i sect.Zakat adalah rukun ketiga dari rukun Islam, yang sangat penting untuk meningkatkan keberadaan ibadah Muslim samping doa dan puasa, sehingga zakat fitrah dilakukan begitu banyak oleh Sekolah Dasar dan Sekolah Dasar Islam untuk digunakan sebagai pembelajaran dasar dengan cara praktek pembayaran zakat di sekolah. Ada dua lembaga pendidikan yang dilakukan oleh penulis. Mereka adalah Bandar II Sekolah Dasar dan Ihsan al-Bandar Sekolah Dasar Islam, Desa Kedung Mulyo, Bandar Kedung Mulyo Kecamatan, Jombang. Pada November 2014 lalu. Tujuan utama dari penelitian ini adalah untuk memahami praktek zakat fitrah diterapkan di Sekolah Dasar dan Madrasah Ibtidaiyah di Bandar Kedung Mulyo Desa, Bandar Kedung Mulyo Kecamatan, Jombang, dan untuk meninjau hukum Syafi'i dan perspektif Maadzhab Hanafi. Dalam penelitian ini menggunakan jenis penelitian empiris dengan pendekatan kualitatif. Sebagian besar data primer dikumpulkan melalui wawancara semi-terstruktur dan observasi lapangan. Sastra dan dokumentasi terkait masalah ini digunakan sebagai data sekunder. Setelah mengumpulkan data, kemudian menganalisisnya dengan menggunakan metode deskriptif kualitatif. Berdasarkan analisis, kesimpulannya adalah zakat fitrah di Sekolah Dasar dan Sekolah Dasar Islam Bandar Kedung Mulyo memiliki karakteristik yang berbeda dan praktek dalam mengumpulkan zakat, distribusi zakat, dan saat pengumpulan dan pembagian zakat. Perbedaannya adalah karena Bandar II Sekolah Dasar cenderung proporsional mengikuti Madzhab Syafi'i dan Hanafi, sedangkan di al-Ihsan Sekolah Dasar Islam cenderung mengikuti atau taqlid pada satu Madzhab, yang Madzhab Syafi'i.